An Early Muqarnas Plaster Ceiling in the Alhambra Palace, Granada - Mc Sweeney, Anna (Edinburgh University Press, 2025)
This case study focuses on one of the earliest plaster muqarnas ceilings in the Alhambra. It is found in the mirador of the Partal, a building also known as the Torre de las Damas, that was built in the first decade of the fourteenth century. This small muqarnas domed ceiling is not widely known and not usually publicly accessible to visitors, but it marks the beginning of a tradition of plaster ceilings at the Alhambra palace that would culminate in the large-scale and widely celebrated ceilings of the Court of the Lions from the latter half of the fourteenth century.1 It sits therefore at a critical point in understanding the history of the Alhambra, marking the early use of a technique that can be linked back to a longer history of plaster ceilings from North Africa and al-Andalus in the twelfth and thirteenth centuries (Figure 20.1). This close examination of the plaster ceiling will explore the techniques and material used in the Partal ceiling, speculate on its origins, its possible function and consider its significance in Nasrid architecture. Particular use will be made of studies that examine the Victoria & Albert Museum’s section of carved wall plaster from the portico of the Partal (Figure 20.2), as well as of recent studies of Nasrid plaster- work in the Alhambra, which can help to illuminate this little-known ceiling.
Stucco in the Islamic World
Keywords: Islamic Studies; Islamic architecture; Islamic art; Medieval Europe; SPAIN; Stucco; al Andalus